2023
DOI: 10.26508/lsa.202201457
|View full text |Cite
|
Sign up to set email alerts
|

SMN promotes mitochondrial metabolic maturation during myogenesis by regulating the MYOD-miRNA axis

Abstract: Spinal muscular atrophy (SMA) is a congenital neuromuscular disease caused by the mutation or deletion of thesurvival motor neuron 1 (SMN1)gene. Although the primary cause of progressive muscle atrophy in SMA has classically been considered the degeneration of motor neurons, recent studies have indicated a skeletal muscle–specific pathological phenotype such as impaired mitochondrial function and enhanced cell death. Here, we found that the down-regulation of SMN causes mitochondrial dysfunction and subsequent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 59 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…Perhaps the best established of these is the role of miR-206 in skeletal muscle maturation and specifically mitochondrial health 80,81 . Furthermore, many studies in SMA have highlighted the essential role of alterations of miRNAs to the SMA phenotype, and these miRNA have also been proposed as biomarkers of Nusinersen response and disease progression 78,8287 . If changes in miRNA expression observed in SMA are a direct or indirect consequence remains to be determined, although one study suggests that SMN is involved in the direct transcription of some microRNAs 82 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps the best established of these is the role of miR-206 in skeletal muscle maturation and specifically mitochondrial health 80,81 . Furthermore, many studies in SMA have highlighted the essential role of alterations of miRNAs to the SMA phenotype, and these miRNA have also been proposed as biomarkers of Nusinersen response and disease progression 78,8287 . If changes in miRNA expression observed in SMA are a direct or indirect consequence remains to be determined, although one study suggests that SMN is involved in the direct transcription of some microRNAs 82 .…”
Section: Resultsmentioning
confidence: 99%
“…This is in-line with previous reports that metabolic maturation in muscle stem cells in partially achieved by miR-1 mediated inhibition of the Dlk-1-Dio3 locus, which contains miRs that repress mitochondrial gene expression 88 . One recent study found that SMN, in combination with MYOD, can regulate the expression of miRNAs that are related to mitochondrial gene regulation, including miR-1 82 . However, we observed this decrease despite detecting similar levels of SMN protein ( Figure 1 C ), suggesting additional levels of regulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The myotube formation ability of C2C12 cells has been used to evaluate the repair and regeneration of muscle after injury [ 4 ]. Numerous studies have evaluated the regulation of muscle atrophy and damage by using differentiated C2C12 myotubes [ 47 , 48 ], and C2C12 myotube diameter was used to assess the myotube formation ability of C2C12 cells [ 4 ]. Notably, C2C12 myoblast cells can differentiate into myotubes and have been used as an in vitro model of skeletal muscle differentiation [ 45 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a disease phenotype was not immediately obvious, persistent low levels of the protein eventually resulted in muscle fiber defects, NMJ abnormalities, poor motor performance, and premature death. Recently, Ikenaka et al found that the down-regulation of SMN causes mitochondrial dysfunction and subsequent cell death in in vitro models of skeletal myogenesis with both a murine C2C12 cell line and human induced pluripotent stem cells [63]. They reported that during myogenesis, a decrease in SMN protein may reduce the production of myoblast determination protein 1 (MYOD1), microRNA (miR)-1 and miR-206, resulting in mitochondrial dysfunction.…”
Section: Smn Protein In Tissues Associated With Sma Pathologymentioning
confidence: 99%